2008
DOI: 10.1158/1535-7163.mct-08-0071
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide sensitizes cancer cells to TRAIL-induced apoptosis via p53-mediated death receptor 4 up-regulation

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 52 publications
7
77
0
Order By: Relevance
“…in rats and found that the blood concentration of andrographolide was approximately 11 mg/mL ($30 mM). At this concentration, andrographolide was reported to possess anti-inflammatory, anti-tumor and anti-thrombotic properties in in vitro studies (Bao et al, 2009;Lu et al, 2011Lu et al, , 2012Zhou et al, 2008). In the present study, our data showed that andrographolide at 50 mM caused CEC death or apoptosis (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 62%
“…in rats and found that the blood concentration of andrographolide was approximately 11 mg/mL ($30 mM). At this concentration, andrographolide was reported to possess anti-inflammatory, anti-tumor and anti-thrombotic properties in in vitro studies (Bao et al, 2009;Lu et al, 2011Lu et al, , 2012Zhou et al, 2008). In the present study, our data showed that andrographolide at 50 mM caused CEC death or apoptosis (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 62%
“…Numerous natural compounds such as triptolide (isolated from the Chinese herb Tripterygium wilfordii Hook), alpha-tocopheryl succinate (a-TOS, an analogue of vitamin E), and andrographolide (a diterpenoid lactone isolated from a traditional herbal medicine Andrographis paniculata) upregulate the expression of DRs directly through the induction of p53. [134][135][136] It has also been reported that ROS participates in the induction of DRs by 6-dehydrogingerdione (a compound isolated from the rhizomes of Zingiber officinale) mediated through expression of p53. 137 However, nimbolide, azadirone, and g-yocotrienol induce DR expression through p53 expression that is mediated by an ERK-p53 mechanism(s).…”
Section: Natural Compounds That Can Sensitize Tumor Cells To Trailmentioning
confidence: 99%
“…1 Both authors contributed equally to this work. 2 ptosis (11). Andrographolide was also shown to interfere with T-cell activation and dendritic cell maturation (12).…”
Section: Recent Studies Have Demonstrated That Transcription Factor Nmentioning
confidence: 99%